A NARRATIVE INQUIRY STUDY ON TEACHING READING USING AUTHENTIC MATERIALS - ., Melasari; Jaelani, Alan; Riana Rahmawanti, Movi (ENGLISH JOURNAL, 2021)
This study investigates in-service English teachers’ voices toward the use of authentic materials in teaching reading and the challenges in using the materials. A narrative inquiry study is employed in which the data were qualitatively collected through interview and documentation process. This study was conducted at one of the Private Junior High Schools in Bogor, Indonesia. An in-service English teacher was chosen as a participant who participated in the process of collecting data through structured interviews by audio recording. The result of this research shows that an in-service English teacher have positive perceptions toward the use of authentic material in teaching reading. Various positive reasons and challenges for the use of authentic materials in the classroom were revealed.